Factors associated to femoral fractures in a cohort study with elderly women (Research, Society and Development, 2021)
Introduction: Femoral fractures in elderly women usually are associated to high morbid-mortability. The purpose of this study was to identify factors associated to femoral fractures in the elderly women (≥ 60 years). Methods: It was a cohort study with elderly women who underwent surgical procedures between 2000 and 2015. We used a socio-demographic/clinical data collection instrument and the European Vertebral Osteoporosis Study Group (EVOS). Data were analyzed by descriptive statistics, Student t-test and Chi-square test with a significance level of p